Инструментальная база управления затратами (Путеводитель предпринимателя, 2020)
In given article are considered tool base of management existing now by expenses. Namely: tools concerning directly to management of expenses, tools in frameworks are considered? Strategic management of expenses?, the tools originating in? To the Japanese system of manufacture?, tools, модульно including management of expenses and общеметодологические tools which are used in management of expenses.